High-entropy nano ceramic fiber reinforced silicon dioxide aerogel and preparation method thereof
By preparing high-entropy nanoceramic fibers and compositeing them in silica aerogel, the problem that high-entropy ceramics are difficult to make nanofibers is solved, and the material is efficiently insulated and toughened at high temperatures is achieved.
Patent Information
- Application Number
- CN202411630738.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to make high-entropy ceramics into nanofibers, limiting their application in silica aerogel thermal insulation materials.
Through the preparation of precursor spinning liquid, electrospinning, high-temperature cracking and sol-gel method, high-entropy nanoceramic fibers were successfully prepared and composited into silica aerogel.
It significantly improves the thermal insulation and toughness of silica aerogel at high temperatures and broadens the application scenarios of materials.
Smart Images

Figure CN119430851A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite materials, and in particular to a high-entropy nano-ceramic fiber reinforced silica aerogel and a preparation method thereof. Background Art
[0002] High entropy ceramics are single-phase solid solutions composed of anions or cations of no less than four elements in equal or non-equimolar ratios. They have high configurational entropy and single-phase rock salt structure, and possess four major effects: "high entropy effect", "lattice distortion effect", "hysteresis diffusion effect" and "cocktail effect". They are a new type of multi-element ceramic co-solution. Compared with traditional high-melting-point ultra-high-temperature ceramics, high-entropy ceramics have higher hardness and elastic modulus. The strong lattice distortion caused by multi-element co-solution makes the stress between maintaining the original configuration greater. The introduction of multi-component atoms leads to local lattice distortion of the material, and the interaction between metal atoms and dislocation structure reduces its elastic strain energy. The distortion generated inside the lattice in high-entropy ceramics increases phonon scattering, and the defects in the solid solution formation process increase the thermal resistance of the ceramics caused by mass and stress field fluctuations, making it show lower thermal conductivity. In addition, the increase in elemental components and the interaction between different elements promote the antioxidant properties of high-entropy ceramics. At the same time, the lower thermal expansion coefficient reduces the possibility of cracking of the material itself and improves its overall stability. In summary, high entropy ceramics are expected to meet the demand for high-temperature resistant (>1500℃) thermal insulation materials.
[0003] Silica aerogel has attracted people's attention due to its unique properties and sol-gel preparation process that can be chemically tailored. It is one of the key research areas in current materials science. Silica aerogel is a nanoporous material, which is formed by drying a wet gel with highly cross-linked Si-O-Si chains. It has a three-dimensional network structure composed of nanoparticles and a gas dispersion medium filled in the structure. Because its solid phase nodes and pore sizes are at the nanoscale, it has many excellent properties such as high porosity, low density, low refractive index, high specific surface area, and low thermal conductivity. Silica aerogel is widely used in insulation materials and other fields. However, the disadvantage of silica aerogel is that it is brittle and not resistant to high temperatures (the thermal conductivity drops significantly above 300°C, and the micro-nano pore structure collapses above 800°C).
[0004] Therefore, if high entropy ceramics are made into nanofibers and composited into silica aerogel insulation materials, it is not only expected to further reduce the thermal conductivity of silica aerogel, but the fibrous structure can also improve the toughness of silica aerogel insulation materials. However, there is no precedent for making high entropy ceramics into nanofibers, so how to make high entropy ceramics into nanofibers has become a technical difficulty. Summary of the invention
[0005] The present invention aims to provide a high-entropy nano-ceramic fiber reinforced silica aerogel and a preparation method thereof. The present invention successfully prepares high-entropy nano-ceramic fibers and composites them in silica aerogel through the steps of preparing a precursor spinning solution, electrospinning, high-temperature pyrolysis, sol-gel method, etc. Precisely because the present invention composites high-entropy nano-ceramic fibers in silica aerogel, the high-entropy nano-ceramic fibers can not only greatly improve the thermal insulation of silica aerogel at high temperatures, but also significantly improve the mechanical properties of silica aerogel such as toughness, thereby broadening the application scenarios of the material.
[0006] The technical solution of the present invention is as follows: In a first aspect, the present invention provides a high entropy nano-ceramic fiber reinforced silica aerogel, which includes silica aerogel as a matrix, and phytic acid-modified high entropy nano-ceramic fibers dispersed in the matrix and bonded to the silica aerogel through hydrogen bonds and chemical bonds.
[0007] The present invention combines high-entropy nano-ceramic fibers with traditional silica aerogels. First, high-entropy nano-ceramic fibers themselves have excellent high-temperature resistance and low thermal conductivity, so they can greatly improve the thermal insulation of silica aerogels at high temperatures; in addition, the present invention also found that after introducing high-entropy ceramics in the form of nanofibers into the three-dimensional network matrix of silica aerogels, the mechanical properties of silica aerogels such as toughness can be significantly improved, thereby broadening the application scenarios of the material.
[0008] On the other hand, the present invention has found in the previous experiments that after the high entropy nano-ceramic fiber is compounded into the silica aerogel, the bonding force between the two is not ideal, so the modification effect of the high entropy nano-ceramic fiber is not significant enough. To this end, the present invention further performs phytic acid surface modification on the high entropy nano-ceramic fiber, and it is found that the bonding strength between the high entropy nano-ceramic fiber and the silica aerogel can be significantly improved. The principle is: phytic acid and the metal on the high entropy nano-ceramic fiber undergo chelation reaction to form a phytic acid complex and precipitate on the fiber surface; the active groups such as hydroxyl, phosphate and ester groups on the phytic acid molecule can also form hydrogen bonds with polar groups in the silica aerogel or condense the hydroxyl groups on the phytic acid molecule and the hydroxyl groups in the raw materials during the synthesis of the aerogel, thereby improving the bonding strength between the high entropy nano-ceramic fiber and the silica aerogel interface.
[0009] Preferably, the high entropy nano-ceramic fiber contains at least four elements of Al, Si, Ti, Zr, Cr, Ni, La, Ce and Y; further preferably, at least four elements of Al, Si, La, Ti, Zr, Ce and Y.
[0010] The present invention finds that, compared with other element combinations, the high entropy nano-ceramic fiber of the above element combination has better properties such as high temperature resistance and thermal conductivity.
[0011] In a second aspect, the present invention provides a method for preparing a high entropy nano-ceramic fiber reinforced silica aerogel, comprising the following steps: S1, adding a high molecular polymer to a high entropy salt solution containing a water-soluble metal salt to obtain a precursor spinning solution; S2, electrospinning the precursor spinning solution into precursor nanofibers; S3, heating and cracking the precursor nanofibers; S4, immersing the high entropy nano-ceramic fiber obtained in S3 in a phytic acid aqueous solution for surface modification to obtain phytic acid-modified high entropy nano-ceramic fiber; S5. Disperse the phytic acid modified high entropy nano-ceramic fiber in water, add an organic silicon source and ethanol, adjust the pH to be acidic, heat and stir, add alkali to neutralize, age, replace the solvent, freeze, and dry to obtain a high entropy nano-ceramic fiber reinforced silica aerogel.
[0012] In the prior art, it is difficult to prepare high entropy ceramics into nanofibers. The present invention adopts electrostatic spinning technology to prepare high entropy nano ceramic fibers. Specifically, in S1, a high entropy salt solution containing a water-soluble metal salt is first mixed with a high molecular polymer to obtain a precursor spinning solution. The role of the high molecular polymer is to provide a fiber skeleton and adjust the viscosity of the spinning solution during the electrostatic spinning process, making it possible to prepare high entropy ceramics into nanofibers.
[0013] In S2, the precursor spinning solution is statically prepared into precursor nanofibers by electrospinning. During the electrospinning process, the precursor spinning solution has suitable fluidity, and after being thrown out from the needle, it forms a precursor nanofiber prototype. In S3, the high temperature removes the polymer skeleton and solvent in the precursor fiber and obtains a good crystalline structure. In S4, phytic acid and the metal on the high entropy nanoceramic fiber undergo a chelating reaction to form a phytic acid complex and precipitate on the fiber surface; the active groups such as hydroxyl, phosphate and ester groups on the phytic acid molecules can also form hydrogen bonds with polar groups in the silica aerogel or produce chemical reactions during the aerogel synthesis process, thereby improving the bonding strength between the high entropy nanoceramic fiber and the silica aerogel interface. In S5, the phytic acid-modified high entropy nanoceramic fiber is mixed with an organosilicon source in a solvent, and the organosilicon source is converted into a silica aerogel by a sol-gel method. During this process, the high entropy nano-ceramic fibers are uniformly dispersed in the system and participate in the formation of a three-dimensional network skeleton in situ, thereby obtaining high entropy nano-ceramic fiber reinforced silica aerogel.
[0014] Preferably, in S1, the high entropy salt solution comprises 1 to 3 parts by weight of a water-soluble salt and 5 parts by weight of an ethanol aqueous solution. Further preferably, the water-soluble salt is four or more of aluminum chloride hexahydrate, sodium silicate, lanthanum nitrate hexahydrate, titanium nitrate, zirconium nitrate pentahydrate, cerium nitrate hexahydrate, and yttrium nitrate hexahydrate.
[0015] Preferably, in S1, the high molecular polymer is selected from at least one of polyvinyl pyrrolidone, polyethylene oxide and polyvinyl alcohol. The concentration of the high molecular polymer in the precursor spinning solution is 0.1-10 wt%.
[0016] The above-mentioned polymers can provide a fiber skeleton and adjust the viscosity of the spinning solution during the electrospinning process, thereby facilitating the preparation of water-soluble salts into nanofibers.
[0017] More preferably, the molecular weight of the high molecular weight polymer is 50,000 to 2,000,000.
[0018] Preferably, in S2, the electrospinning conditions are: spinning voltage 10-30 kV, sol propulsion rate 1-3 mL / h.
[0019] The spinning voltage and sol propulsion rate are mainly used to adjust the thickness of the fiber diameter: charging under the action of a strong electric field generates Coulomb repulsion, thereby overcoming surface tension, electrostatic force, viscoelastic force, gravity and air resistance, and deforming into a cone at the syringe needle to form a Taylor cone. When the electric field strength is large enough, the charged droplets or molten droplets will form a jet stream at the top of the Taylor cone. As the stream leaves the front spinneret, the electric field strength gradually decreases, and the straight jet will stretch, bend, deform and spiral under the action of a series of forces. After the jet undergoes the whipping and solvent evaporation process, the fiber diameter is reduced to hundreds of nanometers or even tens of nanometers.
[0020] Preferably, in S3, the heating cracking is carried out by heating to 800-1600° C. at a rate of 1-20° C. / min under oxygen-containing conditions and keeping the temperature for 1-3 hours.
[0021] Preferably, in S4, the pH of the phytic acid aqueous solution is 5-6.
[0022] The present invention finds that the pH of the phytic acid aqueous solution has a great influence. If the pH is too low, the acid will corrode the fiber surface too deeply, resulting in too low fiber strength; and if the pH is too high, it will affect the subsequent reaction efficiency.
[0023] Preferably, in S4, the ratio of the high entropy nano-ceramic fiber to the phytic acid aqueous solution is 0.3-0.7 g / mL.
[0024] Preferably, in S4, the surface modification temperature is 25-40° C. and the time is 20-40 min.
[0025] Preferably, in S5, the organic silicon source is selected from one or more of tetraethyl orthosilicate, methyl orthosilicate, polysiloxane, methyltrimethoxysilane and methyltriethoxysilane; more preferably tetraethyl orthosilicate, methyl orthosilicate and polysiloxane.
[0026] Preferably, in S5, the phytic acid modified high entropy nano-ceramic fiber is 5 to 10 parts by weight; the water is 20 to 30 parts by weight; the organosilicon source is 8 parts by weight; and the ethanol is 1 to 10 parts by weight.
[0027] The present invention finds that the ratio of the amount of phytic acid modified high entropy nano-ceramic fiber to the amount of the organosilicon source is critical. If the content of phytic acid modified high entropy nano-ceramic fiber is too little, the reinforcing effect is not obvious; on the contrary, if the content is too high, the thermal insulation effect is not ideal due to the decrease in material porosity and the increase in thermal conductivity.
[0028] Preferably, in S5, the pH is adjusted to 3-4 after adding the organosilicon source and ethanol; and the pH is adjusted to 7-8 by heating and stirring.
[0029] In a third aspect, the present invention provides the use of the above-mentioned high entropy nano-ceramic fiber reinforced silica aerogel in the preparation of thermal insulation materials.
[0030] The high entropy nano-ceramic fiber reinforced silica aerogel of the present invention has the following properties: thermal conductivity coefficient at room temperature ≤ 0.02 W / (m·K), and cold surface temperature ≤ 500° C. when the hot surface temperature is 800° C. Therefore, it is particularly suitable for preparing thermal insulation materials.
[0031] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention combines high-entropy nano-ceramic fibers with traditional silica aerogels. First, high-entropy nano-ceramic fibers themselves have excellent high-temperature resistance and low thermal conductivity, so they can greatly improve the thermal insulation of silica aerogels at high temperatures; in addition, the present invention also found that after introducing a proper amount of high-entropy ceramics in the form of nanofibers into the three-dimensional network matrix of silica aerogels, the mechanical properties of silica aerogels, such as toughness, can be significantly improved, thereby broadening the application scenarios of the material.
[0032] (2) The present invention performs phytic acid surface modification treatment on the high entropy nano-ceramic fiber, which can significantly improve the bonding strength between the high entropy nano-ceramic fiber and the silica aerogel.
[0033] (3) The preparation method of the present invention comprises the steps of preparation of a precursor spinning solution, electrospinning, high-temperature pyrolysis, sol-gel method, etc. By rationally selecting the process parameters and sequence of each step, high-entropy nano-ceramic fibers are successfully prepared and composited with silica aerogel. The obtained material has the advantages of low thermal conductivity at room temperature, excellent high-temperature thermal insulation performance, and good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is an electron microscope image of the high entropy nano-ceramic fiber produced by S3 in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with the embodiments.
[0036] Overall embodiment First, a high entropy nano-ceramic fiber reinforced silica aerogel includes silica aerogel as a matrix, and phytic acid-modified high entropy nano-ceramic fibers dispersed in the matrix and bonded to the silica aerogel through hydrogen bonds and chemical bonds. Preferably, the high entropy nano-ceramic fibers contain at least four of Al, Si, Ti, Zr, Cr, Ni, La, Ce, and Y; further preferably, at least four of Al, Si, La, Ti, Zr, Ce, and Y.
[0037] Preferably, the properties of the high entropy nano-ceramic fiber reinforced silica aerogel are as follows: thermal conductivity at room temperature ≤ 0.02 W / (m·K), and cold surface temperature ≤ 500°C when the hot surface temperature is 800°C.
[0038] Secondly, a method for preparing high entropy nano-ceramic fiber reinforced silica aerogel comprises the following steps: S1, adding a high molecular polymer to a high entropy salt solution containing a water-soluble metal salt to obtain a precursor spinning solution.
[0039] Preferably, in S1, the high entropy salt solution comprises 1 to 3 parts by weight of a water-soluble salt and 5 parts by weight of an ethanol aqueous solution; specifically, the water-soluble salt is four or more of aluminum chloride hexahydrate, sodium silicate, lanthanum nitrate hexahydrate, titanium nitrate, zirconium nitrate pentahydrate, cerium nitrate hexahydrate and yttrium nitrate hexahydrate.
[0040] Preferably, in S1, the high molecular polymer is selected from at least one of polyvinyl pyrrolidone, polyethylene oxide and polyvinyl alcohol. The molecular weight of the high molecular polymer is 50,000 to 2,000,000. The concentration of the high molecular polymer in the precursor spinning solution is 0.1 to 10 wt%.
[0041] S2. Electrospinning the precursor spinning solution into precursor nanofibers.
[0042] Preferably, in S2, the electrospinning conditions are: spinning voltage 10-30 kV, sol propulsion rate 1-3 mL / h.
[0043] S3, heating and cracking the precursor nanofibers.
[0044] Preferably, in S3, the heating cracking is carried out by heating to 800-1600° C. at a rate of 1-20° C. / min under oxygen-containing conditions and keeping the temperature for 1-3 hours.
[0045] S4, immersing the high entropy nano-ceramic fiber obtained in S3 in a phytic acid aqueous solution for surface modification to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0046] Preferably, in S4, the pH of the phytic acid aqueous solution is 5-6; the ratio of the high entropy nano-ceramic fiber to the phytic acid aqueous solution is 0.3-0.7 g / mL; the temperature of the surface modification is 25-40° C., and the time is 20-40 min.
[0047] S5. Disperse the phytic acid modified high entropy nano-ceramic fiber in water, add an organic silicon source and ethanol, adjust the pH to be acidic, heat and stir, add alkali to neutralize, age, replace the solvent, freeze, and dry to obtain a high entropy nano-ceramic fiber reinforced silica aerogel.
[0048] Preferably, in S5, the organic silicon source is selected from one or more of tetraethyl orthosilicate, methyl orthosilicate, polysiloxane, methyltrimethoxysilane and methyltriethoxysilane; more preferably tetraethyl orthosilicate, methyl orthosilicate and polysiloxane.
[0049] Preferably, in S5, the phytic acid modified high entropy nano-ceramic fiber is 5 to 10 parts by weight; the water is 20 to 30 parts by weight; the organosilicon source is 8 parts by weight; and the ethanol is 3 to 7 parts by weight.
[0050] Preferably, in S5, after adding the organosilicon source and ethanol, the pH is adjusted to 3-4, and the pH is adjusted to 7-8 by heating and stirring. The heating and stirring temperature is 35-45° C., the rotation speed is 4000-8000 rpm, and the time is 3-5 hours.
[0051] Preferably, in S5, the aging time is 40-60 hours; the solvent for the solvent replacement is water, and the time is 10-20 hours; the freezing temperature is -50 to -30°C; and the drying is vacuum freeze drying.
[0052] Finally, a thermal insulation material is provided, which uses the above-mentioned high entropy nano-ceramic fiber reinforced silica aerogel as raw material.
[0053] Specific embodiments and comparative examples The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0054] The test methods for the samples in the following cases are as follows: (1) Fiber diameter: The fiber diameter was observed using a scanning electron microscope.
[0055] (2) Specific surface area: The specific surface area and pore size analyzer is used to measure the specific surface area of the sample.
[0056] (3) Tensile strength: Tested in accordance with the provisions of GB / T 10295-2008. The sample is a sheet with a size of 300 mm × 300 mm × 15 mm.
[0057] (4) High-temperature thermal insulation performance: A sample with a size of 200 mm × 200 mm × 25 mm was prepared and heated at 800 °C for 10 min. The cold surface temperature was tested. The lower the cold surface temperature, the better the high-temperature thermal insulation performance.
[0058] (5) Mechanical fatigue resistance: After each product is subjected to a cyclic bending test for 1,000 times, observe whether the sample has obvious cracks. If there are no obvious cracks, the mechanical fatigue resistance passes; otherwise, it fails.
[0059] (I) Influence of different element combinations in high entropy nano-ceramic fibers Example 1 S1. Dissolve 2 g of metal nitrate (the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4 in terms of element molar amount) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% polyvinyl pyrrolidone (average molecular weight 500000) with a mass fraction to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0060] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 20 kV, and the sol propulsion rate was 2.0 mL / h.
[0061] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600℃ and kept at 1600℃ for 2h to obtain high entropy nano-ceramic fibers (such as Figure 1 shown).
[0062] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5.5 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0063] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0064] Example 2 S1. Dissolve 2 g of metal nitrate (wherein, in terms of element molar amount, the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), aluminum chloride hexahydrate (Al), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 8% by mass of polyethylene oxide (average molecular weight 100,000) to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0065] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 20 kV, and the sol propulsion rate was 2.0 mL / h.
[0066] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0067] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5.5 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0068] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0069] Example 3 S1. Dissolve 2 g of metal nitrate (wherein, in terms of element molar amount, the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), nickel nitrate hexahydrate (Ni), yttrium nitrate hexahydrate (Y), and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 8% by mass of polyvinyl pyrrolidone (average molecular weight 500000) to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0070] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 20 kV, and the sol propulsion rate was 2.0 mL / h.
[0071] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0072] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5.5 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0073] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0074] Example 4 S1. Dissolve 2 g of metal nitrate (wherein, in terms of element molar amount, the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), sodium silicate (Si), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 8% by mass of polyvinyl alcohol (average molecular weight 50,000) to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0075] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 20 kV, and the sol propulsion rate was 2.0 mL / h.
[0076] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0077] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5.5 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0078] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0079] Comparative Example 1 Comparative Example 1 is basically the same as Example 1, except that there are only two metal elements, as follows: S1. Dissolve 2 g of metal nitrate (wherein, in terms of element molar amount, the molar ratio of zirconium nitrate pentahydrate (Zr) to lanthanum nitrate aqueous solution (La) is 4:1) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% by mass of polyvinyl pyrrolidone (average molecular weight 500000) to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0080] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 20 kV, and the sol propulsion rate was 2.0 mL / h.
[0081] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0082] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5.5 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0083] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0084] The data of the samples obtained in Examples 1-4 and Comparative Example 1 are shown in Table 1: Table 1 The difference between Examples 1-4 and Comparative Example 1 is that the element combinations in the high entropy nano-ceramic fiber are different. From the comparison of the data in Table 1, it can be seen that Examples 1-4 using the four-element combination are significantly better than Comparative Example 1 using the two-element combination in terms of room temperature thermal conductivity and high temperature thermal insulation performance. Furthermore, the element combination "La+Ce+Ni+Y+Zr" of Example 3 is slightly worse than that of Examples 1, 2 and 4 in room temperature thermal conductivity and high temperature thermal insulation performance.
[0085] (II) Influence of different electrospinning process parameters Comparative Example 2 S1. Dissolve 2 g of metal nitrate (the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4 in terms of element molar amount) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% polyvinyl pyrrolidone (average molecular weight 500000) with a mass fraction to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0086] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 8 kV, and the sol propulsion rate was 2 mL / h.
[0087] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0088] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5.5 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0089] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0090] Example 5 S1. Dissolve 2 g of metal nitrate (the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate is 1:1:1:1:4 in terms of element molar amount) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% polyvinyl pyrrolidone (average molecular weight 500000) with a mass fraction to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0091] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 30 kV, and the sol propulsion rate was 2 mL / h.
[0092] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0093] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5.5 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0094] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1 mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0095] Comparative Example 3 S1. Dissolve 2 g of metal nitrate (wherein, in terms of element molar amount, the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% by mass of polyvinyl pyrrolidone (average molecular weight 500000) to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0096] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 50 kV, and the sol propulsion rate was 2 mL / h.
[0097] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0098] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5.5 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0099] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0100] Comparative Example 4 S1. Dissolve 2 g of metal nitrate (the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4 in terms of element molar amount) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% polyvinyl pyrrolidone (average molecular weight 500000) with a mass fraction to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0101] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 30 kV, and the sol propulsion rate was 4 mL / h.
[0102] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0103] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5.5 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0104] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0105] Comparative Example 5 S1. Dissolve 2 g of metal nitrate (wherein, in terms of element molar amount, the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% by mass of polyvinyl pyrrolidone (average molecular weight 500000) to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0106] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 30 kV, and the sol propulsion rate was 0.6 mL / h.
[0107] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0108] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5.5 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0109] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0110] The data of the samples obtained in Examples 1, 5 and Comparative Examples 2-5 are shown in Table 2: Table 2 The difference between Examples 1, 5 and Comparative Examples 2-5 is that the electrospinning process parameters are different. From the comparison of the data in Table 2, it can be seen that the spinning voltage and propulsion rate will affect the diameter and specific surface area of the nanofibers, and then affect the room temperature thermal conductivity, high temperature thermal insulation performance and mechanical fatigue resistance of the material. The results show that the electrospinning process of Comparative Examples 2-5 is poor. For example, compared with Example 1, the spinning voltage of Comparative Example 3 is too high. Although nanofibers can be formed, they are easy to break, and nanofibers that are too short will affect the thermal insulation effect and mechanical fatigue resistance.
[0111] (III) Effect of different phytic acid modification processes Comparative Example 6 S1. Dissolve 2 g of metal nitrate (wherein, in terms of element molar amount, the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% by mass of polyvinyl pyrrolidone (average molecular weight 500000) to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0112] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 30 kV, and the sol propulsion rate was 2.0 mL / h.
[0113] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0114] S4, add 8g high entropy nano-ceramic fiber and 25mL water into a beaker, stir at room temperature for 5h, add 8g ethyl orthosilicate and 5mL ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40℃, stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40℃, and vacuum freeze-dried to obtain high entropy nano-ceramic fiber reinforced silica aerogel.
[0115] Comparative Example 7 S1. Dissolve 2 g of metal nitrate (wherein, in terms of element molar amount, the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% by mass of polyvinyl pyrrolidone (average molecular weight 500000) to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0116] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 20 kV, and the sol propulsion rate was 2.0 mL / h.
[0117] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0118] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 4 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0119] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0120] Example 6 S1. Dissolve 2 g of metal nitrate (wherein, in terms of element molar amount, the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% by mass of polyvinyl pyrrolidone (average molecular weight 500000) to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0121] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 30 kV, and the sol propulsion rate was 2.0 mL / h.
[0122] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0123] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5 at a solid-liquid ratio of 0.5 g / mL, treat at 30° C. for 30 min, rinse with clean water and dry to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0124] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0125] Example 7 S1. Dissolve 2 g of metal nitrate (the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4 in terms of element molar amount) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% polyvinyl pyrrolidone (average molecular weight 500000) with a mass fraction to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0126] S2, high entropy salt fiber precursor spinning solution was used to prepare high entropy salt precursor nanofibers by electrospinning, wherein the electrospinning process conditions were: syringe needle inner diameter 0.86 mm, spinning voltage 30 kV, sol propulsion rate 2.0 mL / h; S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0127] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 6 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0128] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1 mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0129] Comparative Example 8 S1. Dissolve 2 g of metal nitrate (wherein, in terms of element molar amount, the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% by mass of polyvinyl pyrrolidone (average molecular weight 500000) to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0130] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 30 kV, and the sol propulsion rate was 2.0 mL / h.
[0131] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0132] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 6 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 60 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0133] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0134] Comparative Example 9 S1. Dissolve 2 g of metal nitrate (the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4 in terms of element molar amount) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% polyvinyl pyrrolidone (average molecular weight 500000) with a mass fraction to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0135] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 30 kV, and the sol propulsion rate was 2.0 mL / h.
[0136] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0137] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5 at a solid-liquid ratio of 0.5 g / mL, treat it at 60° C. for 5 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0138] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0139] Comparative Example 10 S1. Dissolve 2 g of metal nitrate (wherein, in terms of element molar amount, the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% by mass of polyvinyl pyrrolidone (average molecular weight 500000) to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0140] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 30 kV, and the sol propulsion rate was 2.0 mL / h.
[0141] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0142] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5 at a solid-liquid ratio of 0.5 g / mL, treat at 45° C. for 30 minutes, rinse with clean water and then dry to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0143] S5. Add 8g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0144] The data of the samples obtained in Examples 5-7 and Comparative Examples 6-10 are shown in Table 3: Table 3 The difference between Examples 5-7 and Comparative Examples 6-10 is that the phytic acid modification process parameters are different. From the data comparison in Table 3, it can be seen that the high entropy nano-ceramic fiber in Comparative Example 6 is not modified with phytic acid. Since the combination of high entropy nano-ceramic fiber and silica aerogel is poor, the results show that the tensile strength and mechanical fatigue resistance of the sample are poor. In addition, the pH of the phytic acid aqueous solution, the modification temperature and the modification time will also affect the tensile strength and mechanical fatigue resistance of the material. The results show that the modification process of Comparative Examples 7-10 is poor.
[0145] (IV) Effect of different phytic acid modified high entropy nano-ceramic fiber contents Example 8 S1. Dissolve 2 g of metal nitrate (wherein, in terms of element molar amount, the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% by mass of polyvinyl pyrrolidone to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0146] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 30 kV, and the sol propulsion rate was 2 mL / h.
[0147] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0148] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5.5 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0149] S5. Add 5g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0150] Comparative Example 11 S1. Dissolve 2 g of metal nitrate (wherein, in terms of element molar amount, the molar ratio of lanthanum nitrate hexahydrate (La), cerium nitrate hexahydrate (Ce), titanium nitrate (Ti), yttrium nitrate hexahydrate (Y) and zirconium nitrate pentahydrate (Zr) is 1:1:1:1:4) in 5 g of 50% ethanol aqueous solution to obtain a high entropy salt solution; add 10% by mass of polyvinyl pyrrolidone to the high entropy salt solution and fully dissolve it to obtain a high entropy salt fiber precursor spinning solution.
[0151] S2. High entropy salt precursor nanofibers were prepared by electrospinning the high entropy salt fiber precursor spinning solution, wherein the electrospinning process conditions were: the inner diameter of the syringe needle was 0.86 mm, the spinning voltage was 30 kV, and the sol propulsion rate was 2 mL / h.
[0152] S3, high-entropy salt precursor nanofibers were subjected to high-temperature pyrolysis in air atmosphere, specifically: at 10 °C min -1 The heating rate was increased to 1600°C and kept at 1600°C for 2 h to obtain high entropy nano-ceramic fibers.
[0153] S4. Soak the high entropy nano-ceramic fiber in a phytic acid aqueous solution with a pH value of 5.5 at a solid-liquid ratio of 0.5 g / mL, treat it at 30° C. for 30 minutes, rinse it with clean water and then dry it to obtain phytic acid-modified high entropy nano-ceramic fiber.
[0154] S5. Add 15g of phytic acid-modified high-entropy nano-ceramic fiber and 25mL of water to a beaker, stir at room temperature for 5h, add 8g of ethyl orthosilicate and 5mL of ethanol, add hydrochloric acid (1mol / L) to adjust the pH value to 3, heat at 40°C, and stir at 6000r / min for 4h; then add NaOH aqueous solution (1mol / L) to adjust the pH value to 7, and age in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C, and vacuum freeze-dried to obtain high-entropy nano-ceramic fiber reinforced silica aerogel.
[0155] Comparative Example 12 8g of ethyl orthosilicate, 25mL of water and 5mL of ethanol were added to a beaker, hydrochloric acid (1mol / L) was added to adjust the pH value to 3, heated at 40°C for a certain period of time, and stirred at 6000r / min for 4h; then NaOH aqueous solution (1mol / L) was added to adjust the pH value to 7, and aged in a petri dish for 48h. The product was placed in distilled water to exchange the solvent for 12h, and finally frozen at -40°C and vacuum freeze-dried to obtain silica aerogel.
[0156] The data of the samples obtained in Examples 5, 8 and Comparative Examples 11-12 are shown in Table 4: Table 4 The difference between Examples 5, 8 and Comparative Examples 11-12 is that the amount of phytic acid modified high entropy nano ceramic fiber is different. From the data comparison in Table 4, it can be seen that in Comparative Example 12, no phytic acid modified high entropy nano ceramic fiber is added, that is, pure silica aerogel is used as the thermal insulation material, and the results show that its room temperature thermal conductivity is the lowest, but the high temperature thermal insulation performance and mechanical fatigue resistance are the worst. In Comparative Example 11, due to the excessive content of phytic acid modified high entropy nano ceramic fiber, the room temperature thermal conductivity performance of the thermal insulation material is poor.
[0157] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A high entropy nano-ceramic fiber reinforced silica aerogel, characterized by: The invention comprises a silicon dioxide aerogel as a matrix, and a phytic acid-modified high-entropy nano-ceramic fiber dispersed in the matrix and bonded to the silicon dioxide aerogel through hydrogen bonds and chemical bonds; The high entropy nano-ceramic fiber contains at least four elements of Al, Si, Ti, Zr, Cr, Ni, La, Ce and Y.
2. The high entropy nano-ceramic fiber reinforced silica aerogel according to claim 1, characterized in that: The high entropy nano ceramic fiber contains at least four elements of Al, Si, Ti, Zr, La, Ce and Y.
3. A method for preparing the high entropy nano-ceramic fiber reinforced silica aerogel according to claim 1 or 2, characterized in that include: S1, adding a high molecular polymer to a high entropy salt solution containing a water-soluble metal salt to obtain a precursor spinning solution; S2, electrospinning the precursor spinning solution into precursor nanofibers; S3, heating and cracking the precursor nanofibers; S4, immersing the high entropy nano-ceramic fiber obtained in S3 in a phytic acid aqueous solution for surface modification to obtain phytic acid-modified high entropy nano-ceramic fiber; S5. Disperse the phytic acid modified high entropy nano-ceramic fiber in water, add an organic silicon source and ethanol, adjust the pH to be acidic, heat and stir, add alkali to neutralize, age, replace the solvent, freeze, and dry to obtain a high entropy nano-ceramic fiber reinforced silica aerogel.
4. The preparation method according to claim 3, characterized in that: In S1, the high entropy salt solution includes 1 to 3 parts by weight of a water-soluble salt and 5 parts by weight of an ethanol aqueous solution.
5. The preparation method according to claim 3, characterized in that: In S1, the high molecular polymer is selected from at least one of polyvinyl pyrrolidone, polyethylene oxide and polyvinyl alcohol; The concentration of the high molecular weight polymer in the precursor spinning solution is 0.1-10 wt %.
6. The preparation method according to claim 3, characterized in that: In S2, the electrospinning conditions are: spinning voltage 10-30 kV, sol propulsion rate 1-3 mL / h.
7. The preparation method according to claim 3, characterized in that: In S3, the heating cracking is to increase the temperature to 800-1600°C at 1-20°C / min under oxygen-containing conditions and keep the temperature for 1-3h.
8. The preparation method according to claim 3, characterized in that: In S4, The pH of the phytic acid aqueous solution is 5-6; The ratio of the high entropy nano-ceramic fiber to the phytic acid aqueous solution is 0.3-0.7 g / mL; The surface modification temperature is 25-40°C and the time is 20-40 min.
9. The preparation method according to claim 3, characterized in that: In S5, The phytic acid modified high entropy nano-ceramic fiber is 5 to 10 parts by weight; The organosilicon source is 8 parts by weight; After adding the organosilicon source and ethanol, the pH is adjusted to 3-4; Heat and stir to adjust the pH to 7-8.
10. Use of the high entropy nano-ceramic fiber reinforced silica aerogel according to claim 1 or 2 or the high entropy nano-ceramic fiber reinforced silica aerogel obtained by the preparation method according to any one of claims 3 to 9 in the preparation of thermal insulation materials.
Citation Information
Cited By
Zirconic acid rare earth-based high-entropy ceramic-silicon dioxide fiber membrane for thermal protection of lithium / sodium ion battery and preparation method of zirconic acid rare earth-based high-entropy ceramic-silicon dioxide fiber membrane
CN120006445A
A zirconate rare earth-based high-entropy ceramic-silica fiber membrane for lithium / sodium ion battery thermal protection and a preparation method thereof
CN120006445B
Flexible heat-insulating fibrous ceramic aerogel with core-sheath structure and preparation method of flexible heat-insulating fibrous ceramic aerogel
CN122102710A
Flexible thermal barrier fibrous ceramic aerogel having core-sheath structure and method of making
CN122102710B